Genome wide expression after different doses of irradiation of a three-dimensional (3D) model of oral mucosal - Maria P. Lambros (Genomics Data, 2016)
We evaluated a three-dimensional (3D) human oral cell culture that consisted of two types of cells, oral keratinocytes and fibroblasts as a model of oral mucositis which is a debilitating adverse effect of chemotherapy and radiation treatment. The 3D cell culture model was irradiated with 12 or 2 Gy, and total RNA was collected 6 h after irradiation to compare global gene expression profiles via microarray analysis. Here we provide detailed methods and analysis on these microarray data, which have been deposited in Gene Expression Omnibus (GEO): GSE62395. Keywords: Mucositis, Irradiation, 3D cell culture model, Microarrays, Transcriptional profiling